PENGARUH MOTIVASI DAN BURNOUT TERHADAP KINERJA KARYAWAN BANK KALSEL SYARIAH KCPS BANJARBARU Q MALL - Puji Aulia Rahmi; Lola Malihah; Nur Habibah (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2025)
Improving employee performance is an important factor in achieving organizational goals. Various factors can influence an employee’s performance, such as motivation level , including motivation and burnout. The purpose of this study is to anlyze the extent to which motivation and burnout affect employee performance at Bank Kalsel Syariah KCPS Banjarbaru Q Mall. The approach used in this study is quantitative, where motivation (X1) and burnout (X2) act as independent variables, while employee performance (Y) functions as the dependent variable. The sample used is saturated sampling, by distributing questionnaires to the entire employee population as respondents. The data analysis process in this study includes validity and reliability testing, classical assumption testing, multiple linear regression, as weel as F and, t statistical testing, and calculation of the coefficient of determination. The results show that simultaneously, motivation and burnout significantly affect employee performance (significance value 0.000 < 0.1; Fcount 41.527 > Ftable 2.51). Partially, motivation has a significant effect (significance 0.000 < 0.1; tcount 8.844 > ttable 1.703), while burnout does not significantly affect performance (significance 0.704 > 0.1; tcount 0.384 < ttable 1.703). The coefficient of determination (R²) is 0.755, meaning that motivation and burnout together explain 75.5% of the performance, while the remaining 24.5% is influenced by other factors. This finding highlights the importance of employee motivation and the need to reduce burnout in the workplace..